2018
DOI: 10.3892/etm.2018.5917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probucol on hemodynamics, rheology and blood lipid of diabetic retinopathy

Abstract: The effect of probucol in the treatment of diabetic retinopathy was investigated to analyze its impact on its hemodynamics, rheology and blood lipid. A total of 80 patients with diabetic retinopathy who were treated in the Ninth People's Hospital of Chongqing (Chongqing, China) from January 2015 to August 2016 were selected and divided into two groups by random number table, with 40 patients in each group. Control group was treated by conventional and intensive glycemic control and antihypertensive therapy, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Prior studies have confirmed that a group of CD3 T cells also express CD20 molecules in the body apart from B cells, which have similar and unique biological characteristics to conventional CD3 T cells (26). It has been demonstrated that CD3+CD20+ T cells play an important role in multiple diseases (32), such as rheumatoid arthritis (33,34), multiple sclerosis (32), psoriasis (35), lymphoproliferative disorder (36), and some cancers (31,32). In our study, we further confirmed that NP or MFS treatment decreased CD3+CD20+ T cells in TAO model rats, which could be further decreased via the synergy of NP or MFS combined with NDDM.…”
Section: Discussionmentioning
confidence: 95%
“…Prior studies have confirmed that a group of CD3 T cells also express CD20 molecules in the body apart from B cells, which have similar and unique biological characteristics to conventional CD3 T cells (26). It has been demonstrated that CD3+CD20+ T cells play an important role in multiple diseases (32), such as rheumatoid arthritis (33,34), multiple sclerosis (32), psoriasis (35), lymphoproliferative disorder (36), and some cancers (31,32). In our study, we further confirmed that NP or MFS treatment decreased CD3+CD20+ T cells in TAO model rats, which could be further decreased via the synergy of NP or MFS combined with NDDM.…”
Section: Discussionmentioning
confidence: 95%
“…At present, researches have shown that autoimmune mechanisms, especially abnormal erythrocyte immune function and hemorheology changes, play essential roles in the occurrence and development of TAO [29,30]. Studies have suggested that blood rheology was closely associated with a variety of diseases, such as chronic heart failure [31], sickle cell anemia [32], angina pectoris [33], diabetic retinopathy [34], etc. In our study, we proved that NP or MFS in combination with NDDM could decrease BPC, WBC, brinogen and PV levels.…”
Section: Discussionmentioning
confidence: 99%
“…Venotonic drugs such as ruscus extract and diosmine have been studied to affect leukocyte endothelial interaction and histamine-mediated increase in vascular permeability in the animal model 27 . Probucol has been shown to have positive HR effects on patients with diabetic retinopathy apart from favorable alteration in lipid profile 28 …”
Section: Discussionmentioning
confidence: 99%